2013
DOI: 10.1016/j.plaphy.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Lupinus albus plants acquire mercury tolerance when inoculated with an Hg-resistant Bradyrhizobium strain

Abstract: One strain of Bradyrhizobium canariense (L-7AH) was selected for its metal-resistance and ability to nodulate white lupin (Lupinus albus L.) plants, from a collection of rhizobial strains previously created from soils of the Almadén mining district (Spain) with varying levels of Hg contamination. Plants were inoculated with either strain L-7AH (Hg-tolerant) or L-3 (Hg-sensitive, used as control), and watered with nutrient solutions supplemented with various concentrations (0-200 μM) of HgCl2 in a growth chambe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 34 publications
3
37
1
Order By: Relevance
“…Seeds were inoculated twice (first at sowing and then 1 week later), according to de Lorenzo et al (1994) with 1 ml of the Hgresistant strain L7AH (Ruiz-Díez et al 2012a) or the Hgsensitive strain L3 (Ruiz-Díez et al 2012b) of Bradyrhizobium canariense. Increasing concentrations of HgCl 2 (0-200 μM) were added together with the nutrient solution three times a week and until the end of the experiment (6 weeks), according to Quiñones et al (2013). The conditions in the growth chamber were: a 16 h light/8 h dark photoperiod, 25°C day/15°C night temperature, 58 % relative humidity and an irradiance level of 200 μmol m −2 s −1 .…”
Section: Plant Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…Seeds were inoculated twice (first at sowing and then 1 week later), according to de Lorenzo et al (1994) with 1 ml of the Hgresistant strain L7AH (Ruiz-Díez et al 2012a) or the Hgsensitive strain L3 (Ruiz-Díez et al 2012b) of Bradyrhizobium canariense. Increasing concentrations of HgCl 2 (0-200 μM) were added together with the nutrient solution three times a week and until the end of the experiment (6 weeks), according to Quiñones et al (2013). The conditions in the growth chamber were: a 16 h light/8 h dark photoperiod, 25°C day/15°C night temperature, 58 % relative humidity and an irradiance level of 200 μmol m −2 s −1 .…”
Section: Plant Growthmentioning
confidence: 99%
“…Legumes are well known for their role in maintaining soil fertility due to their capacity to fix atmospheric nitrogen via the legume-Rhizobium symbiosis and, recently, are being considered as a good tool for phytoremediation of Hgcontaminated soils (Quiñones et al 2013). Nitrogen fixation is performed in the root nodules, which are formed by the interaction between rhizobia and the legume root.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, mercury ions can also affect chlorophyll content, activities of root systems, and free proline content in crops (Liu et al, 2004;Deng et al, 2013;Debeljak et al, 2013;Górska-Czekaj and Borucki, 2013;Verbruggen et al, 2009 diverse-defensing mechanisms to cope with heavy metals, such as extrusion, chelation, vacuolar sequestration and regulation of distribution (Verbruggen et al, 2009;Singh et al, 2010;Demim et al, 2013;Huang et al, 2000). Other researches also indicated that mercury ions can bring about severe effects on water transportation in individual plants and plant organs through influencing water channel proteins from a molecular perspective (Daniels et al, 1996;Agre et al, 1998;Zhang et al, 2012); and under the existence of sub-mM levels' HgCl 2 concentrations, water conductance in plant root systems can be 60-90% lower than that of controlled group (Martre et al, 2001;Quiñones et al, 2013). The above-mentioned researches revealed to a certain extent that mercury ions affect the physiological characteristics of various types of crops, such as wheat ), Medicago truncatula (García de la Torre et al, 2013), and maize (Gupta et al, 2012;Muddarisna et al, 2013;Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%